Black Trans Rage and Love: Notes Towards a Method of Revolutionary Life - Fryer-Davis, Valerie (Journal of Critical Race Inquiry)

(untitled) (Queen's University, 2025)
In light of the recent political attacks against trans and Black people worldwide, scholarship has increasingly taken an interest in Black trans critique. However, centering Black trans people in scholarship or activism may expose them to further violence, particularly when the focus is on the death of Black trans women. Shifting the focus away from Black trans death, this article examines how living activists in the present abolish interlinking white supremacy and transphobia. Through case studies of Black trans abolitionists Miss Major and CeCe McDonald, I argue that Black trans love and rage are central to living a revolutionary life that is constantly threatened by the Prison Industrial Complex and other white supremacist transphobic structures. Black trans rage is the fire to live life unbound. It is committed to the abolition of structures that imprison bodies according to gendered and racialized codes, often embracing violence to do so. Black trans rage works in tandem with Black trans love that heals the self and others from the injuries inflicted by white supremacy and transphobia so that one might continue raging. It cultivates community that will sustain the fight for freedom through different forms of love: self-love, agape, philia, storge, and eros. Each of these forms of love are tools for living well under oppression while remaining committed to abolition. Centering Black trans rage and love recognizes the affective resources that Black trans activists offer to revolutionary struggle that will destabilize the capitalist and colonial structures around us.